Effect of gamma irradiation on the oxygen barrier properties in ethyl‐vinyl acetate/ethylene‐vinyl alcohol/ethyl‐vinyl acetate multilayer film. Issue 44 (5th May 2020) - Dorey, Samuel; Gaston, Fanny; Girard‐Perier, Nina; Dupuy, Nathalie; Marque, Sylvain R.A.; Delaunay, Lucie
Abstract: The potential changes of single‐use plastic materials (EVA/EVOH/EVA multilayer film in this study) used in biopharmaceutical and food‐packaging industries are investigated after several gamma irradiation doses: 30, 50, 115, and 270 kGy, and for nonsterilized samples (0 kGy) from a point of view of mechanical properties, thermal properties and permeability properties. Tensile tests, differential scanning calorimetry (DSC), oxygen transmission rate (OTR) and water vapor transmission rate (WVTR) are performed on the multilayer film. For irradiation doses below 50 kGy, thermal and water vapor barrier properties are not altered. For higher doses (50 to 270 kGy), mechanical, thermal and water vapor barrier properties are slightly altered whereas oxygen barrier property decreases from 13 to 27 cm 3 .m −2 .day −1 . This slight change is shown not to happen due to chain entanglement or chain mobility loss in the amorphous phase of the different polymers. It rather comes from a change of the chemical environment of the EVOH layer. Abstract :